ASSESSMENT OF THE FINANCIAL POSITION OF A COMPANY: THEORETICAL ASPECT - Valkauskas, Romualdas (Ekonomika, 2013)
Abstract. The article provides evidence on company’s financial position and its perspectives depending on rational methods of analysis providing reliable and exact evaluations. It is stated that if the absolute and relative financial indicators are not provided, indicator standardization and the analysis of standardized values are not defined, and the complex indicator which shows the synthetic financial position of a company is not presented; without the analysis and assessment of structural changes of the indicator it would be difficult to ensure a company’s successful position in the competitive environment. The article presents methods of analysis of the compound indicator structural changes.Key words: financial position, methods of analysis, analysis of compound indicator structure